ENTERPRENEURSHIP TRAINING IN CHRISTENDOM AND PEACEFULCO-EXISTENCE IN NIGERIA: A SOCIO-ETHICAL ANALYSIS - Remi, Adesanwo Emmanuel (Religions' educator, 2019)
ThispaperisgearedtowardsexaminingtheentrepreneurshiptraininginChristendomandpeacefulcoexistenceinNigeria.No Nation can achieve its socio-religiousarideconomicgrowthwithoutembarkingonentrepreneurshipscheme.Thiswillhelptoimprovethelivingstandardofthe people,and promote religio-economic and the political development among Christians in Nigerian community which is the cardinal objective of Millennium Development Goal(MDGs).Entrepreneurship that couple with peace fulcoexistence open up doors to progressively highlevels of religio-economicandsocio-politicalgrowthamongNigerianChristianCommunity,Thiswillequallyenhanceinnovation,creativity,initiative,visionaryfocus,self-confidence,optimumdisposition,solution to economic empowerment challenges and church future vision accomplishment. Furthermore,peaceful co-existence enhances entrepreneurship and necessary ingredient of security of life and meaningful development in the society.Alsoitisarespectforthelawandorderandtranquilitywhichisbasedonjustice,fairness,fearofGod,harmony,andcares.Similarly,the main objective of this paperistodelvecriticallyintoreligio-economicroleofthe"Ecclesia"(Church)in the economic development among the adherents of ChristianReligion,andimprovementofmoralvaluesintheNigerianSociety.Thisresearch work will adopt explorative and observation methods to elicits our findings.